Enantioselective synthesis of syn/anti-1,3-amino alcohols via proline-catalyzed sequential alpha-aminoxylation/alpha-amination and horner-wadsworth-emmons olefination of aldehydes - Jha, Vishwajeet; Kondekar, Nagendra B.; Kumar, Pradeep (Organic Letters, 2010)
A novel and general method for asymmetric synthesis of both syn/anti-1,3-amino alcohols is described. The method uses proline-catalyzed sequential alpha-aminoxylation/alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes as the key step. By using this method, a short synthesis of a bioactive molecule, (R)-1-((S)-1-methylpyrrolidin-2-yl)-5-phenylpentan-2-ol, is also accomplished.